Pilihan Media Promosi Kesehatan Berdasarkan Kategori Generasi di Rumah Sakit Islam Ibnu Sina Pekanbaru - Imron, Agustiawan (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Health promotion is an effort to spread health information or messages to all levels of society. Achieving health promotion goals generally requires media or tools so that health promotion can be more effective and efficient. The delivery and media of health promotion must be adapted to the characteristics of the target to be achieved. This article discusses the choice of health promotion media by generation category at Ibnu Sina Islamic Hospital Pekanbaru. This study involved 200 patients seeking treatment at the Outpatient Polyclinic from October 1 to 5, 2021. Patients were asked to fill out a questionnaire on Googleform, then the results of the questionnaire were analyzed using the Chi Square or Fisher Exact test, where p < 0.05 was considered significant. This study was dominated by Generation Y (44.0%), college education (54.5%) and male gender (53.5%). Respondents of this study generally chose Instagram as an online health promotion media (61.0%), while leaflets were the media of choice for offline health promotion media (37.5%). Fisher's exact test for the difference between Generasi and health promotion media both online and offline was significant based on statistical tests (p-value = 0.000). There is a difference between the age generation and the choice of health promotion media.